2021
DOI: 10.1101/2021.09.13.459686
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MetaTrass: High-quality metagenome assembly on the human gut microbiome by co-barcoding sequencing reads

Abstract: With the development of sequencing technologies and computational analysis in metagenomics, the genetic diversity of non-conserved region has been receiving increasing attention to unravel complex microbial communities. However, it remains a challenge to obtain enough microbial genome drafts at a high resolution from a microbial community sample. In this work, we presented MetaTrass, a reference-guided assembling pipeline, which exploited both the public microbe reference genomes and long-range co-barcoding in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 70 publications
(80 reference statements)
0
2
0
Order By: Relevance
“…Although we did not compare the assembly results between the stLFR method and TGS method in this study, previous reports have shown the advantages of the stLFR method over TGS in the application of metagenomics. Compared with ONT, the stLFR method generated more species with an NG50 of around 2M and fewer mismatches and INDELs (Qi et al, 2022). Zhang demonstrated that the assembly results based on stLFR data generated more nearcomplete metagenome-assembled genomes than PacBio long-reads in real fecal samples (Zhang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we did not compare the assembly results between the stLFR method and TGS method in this study, previous reports have shown the advantages of the stLFR method over TGS in the application of metagenomics. Compared with ONT, the stLFR method generated more species with an NG50 of around 2M and fewer mismatches and INDELs (Qi et al, 2022). Zhang demonstrated that the assembly results based on stLFR data generated more nearcomplete metagenome-assembled genomes than PacBio long-reads in real fecal samples (Zhang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 3,649.41 Gb of highquality data were obtained from 50 samples for further analysis, with an average sample size of 72.99 ± 17.68 Gb (mean ± S.D.). The high-quality reads were assembled using MetaTrass (Qi et al, 2022), developed for metagenomic stLFR library sequencing data, and the assembled genomes were quantified using CheckM v1.1.2 (Parks et al, 2015). To eliminate redundant high-quality genomes, dRep v3.2.0 (Olm et al, 2017) was employed to construct a catalog of reference genomes, with parameters set to "-pa 0.9 -sa 0.95nc 0.6 -cm larger."…”
Section: Assembly Of Sequencing Data From the Stlfr Library And Const...mentioning
confidence: 99%